Given
L->"Length of the rope"=25mL→Length of the rope=25m
M->"Mass of the man climbing"=72kgM→Mass of the man climbing=72kg
T->"Tension the rope can withstand"=2.9kNT→Tension the rope can withstand=2.9kN
Let the sagging be x m when the man is at the mid point of the rope and the rope then subtends angle thetaθ with the horizontal.
The two vertical components of tension will balance the weight of the man.
So
2Tsintheta=Mxxg2Tsinθ=M×g
sintheta=(Mg)/(2T).....(1)
For theta being small sintheta~~tantheta=x/(L/2)=(2x)/L
Now imposing approximation the relation (1) becomes
(2x)/L=(Mxxg)/(2T)
=>x=(MxxgxxL)/(4T)
=>x=(72xx9.8xx25)/(4xx2900)~~1.52m
Without approximation the realation (1) can be written as
x/sqrt(x^2+(L/2)^2)=(Mxxg)/(2T)
=>(x^2+(12.5)^2)/x^2=((2xx2900)/(72xx9.8))^2=67.57
=>1+156.25/x^2=67.57
=>156.25/x^2=67.57-1=66.57
=>x^2=156.25/66.57
=>x=sqrt(156.25/66.57)~~1.53m
Another way of calculation
From (1)
theta=sin^-1((Mxxg)/(2T))=sin^-1((72*9.8)/(2*2900))
theta=6.99^@
So
(2x)/L=tantheta=tan6.99
x=(25xxtan6.99)/2=1.53m